Occupational Safety Culture and Zero Accidents: Implications Company Reputation - Lukis Tiantono; Survival Survival; Nasharuddin Mas (Information Technology and Science (ITScience), 2026)
Occupational Safety and Health (OHS) is not only a regulatory obligation but also a crucial element influencing a company's reputation. A positive corporate reputation can be supported by strong OHS performance, as evidenced by companies receiving the Zero Accident Award. However, empirical studies investigating the relationship between OHS programs, OHS culture, Zero Accident achievement, and corporate reputation are still rare, especially in Indonesia. This study aims to analyze the role of OHS program implementation and OHS culture in achieving Zero Accidents and their impact on corporate reputation.The research approach used was quantitative, using a survey method. Respondents included 333 employees from 20 Zero Accident Award-winning companies in the Greater Malang area. Data collection was conducted using a questionnaire, and data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to test the direct and indirect (mediation) effects between variables.The analysis results show that the implementation of the OHS program and OHS culture have a positive and significant impact on the achievement of Zero Accidents and the company's reputation. Achieving Zero Accidents has also been shown to have a positive and significant impact on the company's reputation. Furthermore, the Zero Accident variable acts as a mediator that strengthens the influence of the OHS program and OHS culture on reputation. These findings confirm that OHS implementation is not merely a matter of complying with regulations, but rather a strategic investment to reduce workplace accidents and build a positive company image sustainably.